Characterization of Oryzias latipes glucocorticoid receptors and their unique response to progestins. Issue 3 (23rd July 2014) - Miyagawa, Shinichi; Lange, Anke; Tohyama, Saki; Ogino, Yukiko; Mizutani, Takeshi; Kobayashi, Tohru; Tatarazako, Norihisa; Tyler, Charles R.; Iguchi, Taisen
Abstract Various receptor bioassays, including estrogens, androgens and thyroid hormones, have been developed and applied successfully for assessing hormone function in a wide range of animal species, including fish. In fish, corticosteroids play a pivotal role in physiology as they do in mammals, but far less is known about the corticosteroid receptor system in fish compared with in mammals. Here we established a transient transactivation assay using the Japanese medaka, Oryzias latipes, glucocorticoid receptors (olGRs) and mineralocorticoid receptor to analyse their functional properties in a fish. We found that olGR2 was highly responsive to glucocorticoids, similar to the human GR, whereas the olGR1 subtype was minimally responsive. Thus, olGR2 most likely mediates glucocorticoid signaling in medaka. We further tested crosstalk between GRs and other steroid hormones, and found that progestins could activate or inactivate olGR2‐mediating transcription, depending on the presence or absence of cortisol. The transactivation assays developed for medaka GRs provide tools to gain useful insights into corticosteroid signaling in fish and for in vitro screening of environmental substances activating GRs. Copyright © 2014 John Wiley & Sons, Ltd.